Automatic Aquarium Cleaner and Fish Feeder Based on Microcontroller Atmega8535 - Perangin-angin , Bisman; Ginting, Teopilus Andri Putra (Talenta Publisher, 2021)
The design of an aquarium cleaner and automatic fish feeder based on the Atmega8535 microcontroller has been successfully carried out. Testing is carried out after all components are integrated into one including the overall program that has been made. Testing is done by running the system according to the procedure and observing the system's performance, starting with measuring turbidity and checking the water replacement schedule. The work processes running on the system are analyzed after testing. When the water turbidity level is high, the drain pump will activate and pump water out of the aquarium. After the remaining water level is about 25%, the drain pump will stop, and the filling pump will be active. The fill pump runs until the water level reaches 100% and then shuts down. After 10 minutes of filling the water, the servo motor will move and drop the fish feed into the aquarium.